The phenomenon of the VOX party in the context of national and cultural development of Spain - A. Kozhanovsky (Ибероамериканские тетради)
The article discusses the last electoral successes of “Vox” (Spanish right-wing conservative party) whose achievement came as a surprise to most analysts. The author of the article considers “Vox” phenomenon from the point of view of national and cultural processes in post-Franco Spain. He thinks it possible to see here among other things the reaction of part of Spanish society to the “identity crisis” which they are now experiencing.